Analisis Peran Media Sosial dalam Peperangan Rohani (Spiritual Warfare): Strategi Pelayanan Digital dalam Menghadapi Disinformasi yang Mengikis Spiritualitas Kristen - Pujiwati Pujiwati (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study examines the role of social media as an arena for contemporary spiritual warfare and its impact on Christian spirituality, particularly in the context of increasing digital misinformation. Using a mixed-methods approach, this research combines quantitative surveys and qualitative interviews to identify patterns of religious misinformation dissemination and its impact on doctrinal understanding, worship practices, and the faith identity of the congregation. The findings indicate that exposure to misinformation negatively affects the depth of spiritual practices, increases theological confusion, and creates